2007
DOI: 10.1021/ja072747w
|View full text |Cite
|
Sign up to set email alerts
|

[1]Molybdarenophanes:  Strained Metallarenophanes with Aluminum, Gallium, and Silicon in Bridging Positions

Abstract: The first [1]molybdarenophanes were synthesized and structurally characterized. The aluminum and gallium compounds [(Me2Ntsi)Al(eta6-C6H5)2Mo] (2a) and [(Me2Ntsi)Ga(eta6-C6H5)2Mo] (2b) [Me2Ntsi = C(SiMe3)2(SiMe2NMe2)] were obtained from [Mo(LiC6H5)2].TMEDA and (Me2Ntsi)ECl2 [E = Al, Ga] in analytical pure form with isolated yields of 74% (2a) and 52% (2b). The silicon-bridged species [Ph2Si(eta6-C6H5)2Mo] (2c) was synthesized from [Mo(LiC6H5)2].TMEDA and Ph2SiCl2. Compound 2c was isolated as a crystalline mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
(62 reference statements)
2
36
0
1
Order By: Relevance
“…For example, for [1]chromarenophanes the difference is 1.4°[Al: 11.81(9)°; Ga: 13.24(13)°], 10c whereas for [1]molybdarenophanes, equipped with the same bridging moiety E(Me 2 Ntsi) (Chart 2), the difference amounts to 3.0°[Al: 18.28(17)°; Ga: 21.24(10)°]. 11 The measured difference of only 0.6°for [1]ruthenocenophanes 7a and 7b is surprisingly small [Al: 20.31 (19)°; Ga: 20.91 (19)°]. 12 Based on the difference of 3.0°found for [1]molybdarenophanes, the calculated difference of 3.3°for 7a and 7b matches with the expectation better than the experimentally determined difference of only 0.6°.…”
Section: Methodsmentioning
confidence: 99%
“…For example, for [1]chromarenophanes the difference is 1.4°[Al: 11.81(9)°; Ga: 13.24(13)°], 10c whereas for [1]molybdarenophanes, equipped with the same bridging moiety E(Me 2 Ntsi) (Chart 2), the difference amounts to 3.0°[Al: 18.28(17)°; Ga: 21.24(10)°]. 11 The measured difference of only 0.6°for [1]ruthenocenophanes 7a and 7b is surprisingly small [Al: 20.31 (19)°; Ga: 20.91 (19)°]. 12 Based on the difference of 3.0°found for [1]molybdarenophanes, the calculated difference of 3.3°for 7a and 7b matches with the expectation better than the experimentally determined difference of only 0.6°.…”
Section: Methodsmentioning
confidence: 99%
“…[2a, 3] An interesting class of ferrocene derivatives is represented by [n]ferrocenophanes. [5] Despite the large and rapidly increasing number of existing strained [n]ferrocenophanes, [6] only species with two or more atoms in the bridge, such as the 17-electron carbon-bridged [2]ferrocenophanium ions in 1 and 2, have been successfully synthesized by oxidation and isolated as stable salts. [5] Despite the large and rapidly increasing number of existing strained [n]ferrocenophanes, [6] only species with two or more atoms in the bridge, such as the 17-electron carbon-bridged [2]ferrocenophanium ions in 1 and 2, have been successfully synthesized by oxidation and isolated as stable salts.…”
mentioning
confidence: 99%
“…[4] Among these, the most explored are strained silicon-bridged [1]ferrocenophanes or sila[1]ferrocenophanes, because of their diverse reactivity and ability to be converted into polyferrocenylsilanes (PFSs) by a variety of ring-opening polymerization (ROP) methods. [5] Despite the large and rapidly increasing number of existing strained [n]ferrocenophanes, [6] only species with two or more atoms in the bridge, such as the 17-electron carbon-bridged [2]ferrocenophanium ions in 1 and 2, have been successfully synthesized by oxidation and isolated as stable salts. [7] To date, only electrochemical studies of the one-electron oxidation of [1]ferrocenophanes have been reported.…”
mentioning
confidence: 99%
“…A related galla[1]ferrocenophane was published by Lund et al (2006). For related literature, see: Bellas & Rehahn (2007) ;Foucher et al (1992); Herbert et al (2007); Lund et al (2007); Osborne & Whiteley (1975); Schachner et al (2005aSchachner et al ( , 2007.…”
Section: Related Literaturementioning
confidence: 99%